2013
DOI: 10.1016/j.cca.2012.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of N-terminal fragment of precursor protein brain-type natriuretic peptide (NT-proBNP) in twin pregnancy

Abstract: Twin pregnancy differs considerably from singleton pregnancy in many aspects and it is unknown how serum NT-proBNP level behaves in women with twin pregnancies. Serum NT-proBNP levels were determined longitudinally at gestational weeks (GW) 24 and 35 in normotensive women with 13 twin and 99 singleton pregnancies. The effects of maternal demographic characteristics on NT-proBNP levels were also analyzed. The serum NT-proBNP levels (pg/mL) in twin pregnancies, which were not different from those in singleton pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In addition, as the serum NT‐proBNP level was reported to increase in women at higher risk of PPCM, i.e. women with MFP and women with HD, the results of the present study regarding NT‐proBNP were expected, and this variable may be a good choice for blood tests to detect women at higher risk of PPCM. However, the NT‐proBNP level was much lower in women with MFP/HD compared with that reported in patients with PPCM .…”
Section: Discussionmentioning
confidence: 52%
“…In addition, as the serum NT‐proBNP level was reported to increase in women at higher risk of PPCM, i.e. women with MFP and women with HD, the results of the present study regarding NT‐proBNP were expected, and this variable may be a good choice for blood tests to detect women at higher risk of PPCM. However, the NT‐proBNP level was much lower in women with MFP/HD compared with that reported in patients with PPCM .…”
Section: Discussionmentioning
confidence: 52%
“…As gestational weight gain and blood volume expansion are greater in twin than singleton pregnancies,7 8 cardiac overload may be more likely to occur and the serum precursor protein BNP (NT-proBNP) level in the late stage of pregnancy is significantly higher in twin than singleton pregnancies 9. In addition, plasma BNP level is higher for hypertensive than for normotensive pregnant women 10.…”
Section: Discussionmentioning
confidence: 99%
“…This condition leads to water and sodium excretion from the kidneys when increased volume and resistance occur. Studies have shown that N-terminal probrain natriuretic peptide (NT-proBNP) levels increase in cases of preeclampsia, hypertensive pregnancies, twin pregnancies, and pregnancies complicated with pulmonary or cardiac disorders [8][9][10][11]. Previous studies usually focused on patients with preeclampsia and established final and accurate diagnoses.…”
Section: Introductionmentioning
confidence: 99%